Fuzzy Piecewise-objective Programming Approach for Integrated Supplier Selection and Production Planning Problems Considering Discounts and Fuzzy Parameters: the Static Case - Adhina Rizkillah Harahap; Sutrisno Sutrisno; Redemtus Heru Tjahjana; Widowati Widowati (Jurnal Sistem Informasi Bisnis, 2025)
In the manufacturing and retail sectors, the challenge of supplier selection revolves around efficiently allocating the necessary amount of raw materials to each supplier to minimize procurement costs. Concurrently, production planning focuses on maximizing output. To achieve maximum revenue, decision-makers must make optimal decisions in both areas. This paper introduces a new mathematical model, falling within the fuzzy piecewise programming domain, to support decision-making in supplier selection and production planning. It addresses integrated supplier selection and production planning issues, incorporating discounts and fuzzy factors. The aim is to optimize supply chain performance, ultimately maximizing the production activity profit. The model accommodates scenarios involving multiple raw materials, suppliers, products, and buyers. Through numerical experiments, the effectiveness of the proposed model is evaluated, demonstrating its ability to provide the optimal solution. Thus, it can be readily applied by industry decision-makers and managers.